Risk of credit - Jiménez Sotelo, Renzo (2003)
Traditional risk definitions, based on supervisor’s point of view, don’t beholdexplicitly the existence and interaction of other important risks such as derivativecredit risks from other unsecured risk by debtors of bank system in economiespartially “dollarized”. One of these critical risks is derivative credit risk fromexchange risk, which hasn’t been stated directly in doctrine proposed by Basel Committee.This paper settles basic criteria to analyze this risk and describes the principal consequences of issuing debt in a different currency, over credit rating, provisionsand the economic capital that must be assigned in the financial entities (whosecustomers debt show gap currency). These regulations encourage introducingas soon as possible aggressive mechanisms of global and quantitative managementof risk into the financial system, non-existent in countries like Peru.